2022
DOI: 10.1017/sjp.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Locating the Dark Triad in a Multidimensional Personality Space

Abstract: The Dark Triad traits of Psychopathy, Machiavellianism, and Narcissism should be clearly recognizable within a multidimensional personality space. Two such personality spaces were investigated in this study: HEXACO (Honesty-Humility, Emotionality, Extraversion, Agreeableness, Conscientiousness, and Openness to Experience); and the Zuckerman-Kuhlman-Aluja Personality Questionnaire (ZKA-PQ) space (Extraversion, Neuroticism, Activity, Sensation Seeking, and Aggressiveness). Our sample comprised 289 participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 94 publications
(137 reference statements)
3
8
0
Order By: Relevance
“…The Dark Triad and Empathy (both cognitive and affective) do appear in the same 2D space, at an angle of 180 degrees to each other. The pattern of correlation within the Dark Triad Dirty Dozen (DTDD) that we reported here, at least for an adult population, both matches that which we have recently reported (Naor-Ziv et al, 2022) using the Short Dark Triad (SD3), and is similar to the pattern of correlation reported by Dinić et al (2018) for their Serbian versions of the DTDD – though they reported a somewhat higher correlation between Narcissism (N) and Machiavellianism (M). Conceivably, this is due to the fact that they employed a 7-point scale (e.g., Martin, 1978).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The Dark Triad and Empathy (both cognitive and affective) do appear in the same 2D space, at an angle of 180 degrees to each other. The pattern of correlation within the Dark Triad Dirty Dozen (DTDD) that we reported here, at least for an adult population, both matches that which we have recently reported (Naor-Ziv et al, 2022) using the Short Dark Triad (SD3), and is similar to the pattern of correlation reported by Dinić et al (2018) for their Serbian versions of the DTDD – though they reported a somewhat higher correlation between Narcissism (N) and Machiavellianism (M). Conceivably, this is due to the fact that they employed a 7-point scale (e.g., Martin, 1978).…”
Section: Discussionsupporting
confidence: 90%
“…Our regional analysis of the 2D representation not only reveals that the Dark Triad and empathy are at an angle of 180 degrees to each other but also suggests that even when there are discrepancies between self-report and parent-report regarding empathy (Johnson et al, 2009), these are nevertheless aligned within the same 2D space. Furthermore, while one can debate to what degree Psychopathy (P) and Machiavellianism are actually separable (Muris et al, 2017, p. 188; Rogoza et al, 2019, p. 174; Vize et al, 2018, p. 109), in the 2D SSA spaces presented here they are in close proximity but are not coincident (in line with Naor-Ziv et al, 2022).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thornquist and Zukerman (1995) found psychopathy, using Hare's revised psychopathy checklist (PCL-R; Hare et al, 1991), to be related to increased sensation seeking and aggressiveness. Utilizing the dark triad (DT), psychopathy has been linked positively to aggressiveness, sensation seeking, and neuroticism (Aluja et al, 2022;Noar-Ziv, Glicksohn, and Aluja, 2022). While Moore, Ross, and Brosius (2020) report a strong association between DT psychopathy and triarchic psychopathy (r = .73), triarchic boldness has moderate positive associations with extraversion (FFM) and negative associations with neuroticism (FFM; Collison, Miller, & Lynam, 2021;Drislane et al, 2022;Stanley, Wygent, & Sellbom, 2013) which are not shown in FFM evaluations of DT psychopathy (Douglas, Bore, & Munro, 2012;O'Boyle et al, 2014;Veselka, Schermer & Vernon, 2012).…”
Section: Psychopathy Within the Affmmentioning
confidence: 99%
“…Moreover, these associations are somewhat different in comparison with the other two traits of the Dark Triad, i.e., Machiavellianism and psychopathy, since, in general, these seem to relate positively to neuroticism and negatively to conscientiousness, openness to experience, and agreeableness. In the case of extraversion, Machiavellianism seems to relate negatively and psychopathy positively [40][41][42][43][44][45][46][47]. Following this idea, the study by Pruysers et al [6] is the only one located that has analyzed the relationship of civic engagement with both the traits considered to be more general and the traits considered to be more socially undesirable.…”
Section: Introductionmentioning
confidence: 99%